2014
DOI: 10.1080/10926771.2014.956916
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Appetitive Aggression in Rwandan Genocide Perpetrators

Abstract: The objectives of this study were to investigate rates of posttraumatic stress disorder (PTSD) KEYWORDS appetitive aggression, combat trauma, exposure to violence, genocide, perpetrators, posttraumatic stress disorder, RwandaDuring the genocide in Rwanda in 1994, it is estimated that nearly 1 million people were murdered over the course of 3 months. Fighting erupted between two artificially divided "ethnic" groups, the Hutu majority and the Tutsi minority. The main goal of the perpetrators of the genocide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…The results of the present study indicate that only a few perpetrators (18.9%) identified an event during which they had perpetrated violence as the most distressing event to which their PTSD symptomatology referred, indicating that perpetrating violence is perceived as traumatic for some combatants, but not for all. This finding aligns with previous studies that showed that only a minority of perpetrators indicated an event that they had perpetrated as their most frightening event (Schaal et al, 2014 ). However, in the present study, those ex-combatants who indicated a perpetrated violent act as their index trauma were significantly more affected by DSM-5 PTSD compared to those who reported an event from the traumatic event list.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study indicate that only a few perpetrators (18.9%) identified an event during which they had perpetrated violence as the most distressing event to which their PTSD symptomatology referred, indicating that perpetrating violence is perceived as traumatic for some combatants, but not for all. This finding aligns with previous studies that showed that only a minority of perpetrators indicated an event that they had perpetrated as their most frightening event (Schaal et al, 2014 ). However, in the present study, those ex-combatants who indicated a perpetrated violent act as their index trauma were significantly more affected by DSM-5 PTSD compared to those who reported an event from the traumatic event list.…”
Section: Discussionsupporting
confidence: 92%
“…However, most studies have not investigated whether the trauma related symptoms of those who engaged in violence were related to self-perpetrated or self-experienced events. A recent study of Rwandan perpetrators found that only a few indicated a perpetrated event as the index trauma to which their PTSD symptomatology referred (Schaal, Heim, & Elbert, 2014 ).…”
mentioning
confidence: 99%
“…Si bien la mayoría de los estudios que emplean la B-RCOPE han sido llevados a cabo en Estados Unidos (Pargament et al, 2011), se han registrado numerosos desarrollos en diferentes contextos, como Alemania (Zwingmann, Müller, Körber, & Murken, 2008;Zwingmann, Wirtz, Müller, Körber, & Murken, 2006), Brasil (Freitas et al, 2015;Ramirez et al, 2012), Canadá (Houck, 2012), Corea (Noh, Chang, Jang, Lee, & Lee, 2016), Croacia (Mihaljević, Aukst-Margetić, Vuksan-Ćusa, Koić, & Milošević, 2012), España (Martinez & Sousa, 2011), Francia (Caporossi, Trouillet, & Brouillet, 2012), Grecia (Kapsou, Panayiotou, Kokkinos, & Demetriou, 2010), Holanda (Braam et al, 2008, India (Grover, Sarkar, Bhalla, Chakrabarti, & Avasthi, 2016;Roberts & Montgomery, 2015), Inglaterra (Brewer, Robinson, Sumra, Tatsi, & Gire, 2015;Thuné-Boyle et al, 2013) Uwakwe, Aguocha, et al, 2016;Amadi, Uwakwe, Ndukuba, et al, 2016), Nueva Zelanda (Gardner, Krägeloh, & Henning, 2014), Pakistán (Khan & Watson, 2006) (Schaal, Heim, & Elbert, 2014), Suiza (Fitchett, Winter-Pfandler, & Pargament, 2014) y Tanzania (Watt et al, 2014). Los estudios que emplean la escala RCOPE han utilizado muestras de población adolescente y adulta, tanto religiosa como no religiosa, lo que contribuye a confirmar el modelo propuesto por el autor.…”
Section: Introductionunclassified
“…If endorsing having enjoyed violence in the context of war is positively associated with PTSD, depression, and guilt as a main effect, and if enjoying violence did not moderate the impact of trauma exposure on these outcomes, then this would suggest that a moral injury framework is most useful in understanding the impact of using violence in combat on this population (Griffin et al, 2019; Litz et al, 2009; Purcell et al, 2018). On the other hand, if endorsing enjoying violence serves as a moderator by decreasing the impact of combat on these trauma-related outcomes, this would suggest that the framework of the hunting network and appetitive aggression could be helpful in understanding postcombat emotional sequalae in this population (Köbach et al, 2014, 2015; Moran et al, 2014; Nandi et al, 2015; Schaal et al, 2014; Weierstall & Elbert, 2011; Weierstall, Huth, et al, 2012; Weierstall et al, 2011).…”
mentioning
confidence: 99%
“…Yet there is also a body of research suggesting violence in war can sometimes be associated with positive affective states that persist beyond the moment of violence, such that perpetrating cruelty or killing an enemy can become intrinsically rewarding and thus self-perpetuating (Köbach et al, 2014, 2015; Moran et al, 2014; Nandi et al, 2015; Schaal et al, 2015, 2014; Weierstall & Elbert, 2011; Weierstall, Huth, et al, 2012; Weierstall et al, 2015, 2011). This idea that engaging in highly aggressive acts can be exciting and pleasurable has been termed “appetitive aggression,” and has typically been investigated in areas of the world that have experienced protracted war and genocide (e.g., German WWII soldiers, Weierstall, Huth, et al, 2012; Democratic Republic of the Congo, Köbach et al, 2014; Burundi, Crombach & Elbert, 2014; Köbach et al, 2015; Nandi et al, 2016; Uganda, Weierstall, Schalinski, et al, 2012).…”
mentioning
confidence: 99%